Good practice of Community Model for Everyday-Life based on the Sufficiency Economy Philosophy in Maha Sarakham - Atthakorn , Suthinee; Ieamvijarn, Subunn (Journal for Developing the Social and Community, 2022)
The objectives of this was to find good practices within the studied communities on behavior related to the sufficiency economy philosophy in a sustainable matter. The study was conducted in 3 villages in Maha Sarakham province: Ban Nong Phueak (Wapi Pathum District); Ban Lao Noi (Muang District); and Ban Huai Sai (Borabue District). The respondents were 20 community leaders. The tool used for data collection was In-depth interview and focused-group discussion. Qualitative data analysis by content analysis. The findings showed that the good practice within the included villages showed that in order to carry out sufficiency economy philosophy in a sustainable way, these would be needed: (1) strong leadership and good role model; (2) collaborations amongst community members and capacity to participate in development for better living conditions; (3) good followership amongst community members who have a sense of ownership leading to application of knowledge on sufficiency economy philosophy on their lives with haste and ease; (4) Development and improvement of quality of life amongst group members which derived from consensus leading to group synergy; (5) Development of model based on group’s previous experience which provide knowledge and encouragement to others who aspire to have improving quality of life and way of living; (6) Group members have adopted the philosophy of sufficiency economy to use in their way of life leading to sustainability and happiness through moderate consumption and production of goods; (7) Presence of learning from previous action and knowledge management within the group which can lead to further development and refinement of ideas and its operations; and (8) The group members have open-mind attitude resulting in good practice in adopting behaviors reflecting the philosophy of sufficiency economy through acceptance to learn and develop.